Prevalence of healthy diet and activity behaviours among U.S. Latino preschool children living in an emerging Latino community - Carli A. Liguori; Neil P. Sharma; Patricia I. Documét; Bethany B. Gibbs; Sharon E. Taverno Ross (Journal of Nutritional Science, 2023)
This pilot study provides preliminary insights into whether Latino preschool children living in an emerging Latino community (ELC) are meeting recommendations for healthy diet and activity behaviours and whether those behaviours are associated with sociodemographic or home environment variables. Secondary data analysis was conducted utilising cross-sectional baseline survey data from ANDALE Pittsburgh, a home-based intervention study. Measures included parent-reported information on child dietary intake, screen time and the home environment, and objectively measured physical activity and anthropometry. χ2 and Fischer's exact tests were used to determine associations. The study was conducted in an ELC in western Pennsylvania in the US. Fifty-one Latina mothers (age: 33⋅5 ± 6⋅1 years; 63 % Mexican origin; 86 % low acculturation) and their children (age: 3⋅9 ± 1⋅3 years; 55 % male) 2–5 years of age. On average, children consumed 2⋅25 ± 1⋅44 cups of fruits/vegetables, viewed 98⋅7 ± 74⋅2 min of screen time, accumulated 12⋅9 ± 2⋅9 min/h of total physical activity and consumed 15⋅5 ± 26⋅0 kcals of sugar-sweetened beverages per day. Forty-one percent met the fruit/vegetable recommendation, 54 % met the screen time recommendation, 27 % met the physical activity recommendation and 58 % met the sugary drink recommendation. Country of origin (P = 0⋅032) and acculturation (P = 0⋅048) were significantly associated with children meeting sugary drink recommendations. No other relationships were significant. The proportion of children in this sample meeting diet and activity recommendations was mixed. More research with larger sample sizes is needed in ELCs to identify effective intervention strategies for improving health behaviours.